King Henry VIII and his relationship with the papacy - Dr. Adnan Salih Mohammad (Journal of College of Education, 2024)
The relation of Henry Vlll′s to the popery is one of the ‎important subjects of which the Arabic reader does not know ‎much in spite of the contact between Britain and the Arab ‎world in general and Iraq in particular. Henry Vlll′s divorce of Catherine of Aragon was the direct ‎reason, for the conflict between England and the Popery. In ‎addition to this divorce there were other important reasons that ‎were not less effective then it and they gathered momentum ‎with the passage of time and led England to break her ‎relations with the popery. The popes policy were contradictory with the national ‎ambitions. the popeis authority in imposing taxes and in the ‎judicial issues was contradicted with the national spirit and ‎Henry Vlll′s will to establish power in his country. The people of England preferred the nationalization of the ‎church in their country and putting an end to the power of the ‎clergy men who were an independent body like a state with in ‎the state and they only. followed their pope ; they did not pay ‎anything to the state, hence the public opinion was ready to ‎support the in dependence of the king dome from the church of ‎Rome.